Broken framing an assessment of news coverage of disabilities by the Philippine Daily Inquirer and the Philippine Star from 2010-2012 - Abique, Eunice T.; Chua, Yvonne T.; University of the Philippines. College of Mass Communication (2013)
"The issue of persons with disabilities (PWDs) goes beyond their physical limitation. It is social and environmental factors that disable an individual and hinder one from fully participating in the society. In 2006, the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) called for the proper portrayal of PWDs in media. However, stereotypes and misrepresentation still exist in the media today. To examine the current coverage of PWDs in the Philippines, this thesis looked at the articles published by the Philippine Daily Inquirer and the Philippine Star, two of the leading newspapers in the country. Using the Agenda-Setting Theory, Framing Theory of Media and the Social Media of Disability, the researchers assessed how media outfits affect the coverage and representation of PWDs. While the content analysis results revealed that coverage of the two newspapers take on the human-rights perspective in the coverage, leaders of various PWD organizations noted that there is still a great need to improve it. Traditional perspectives in viewing PWD issues are still used in the print media, such as medical and charity perspective."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: People with disabilities -- In mass media -- Philippines; Philippine newspapers